2017
DOI: 10.1177/1558944717744334
|View full text |Cite
|
Sign up to set email alerts
|

Irreducible Galeazzi Fracture-Dislocations

Abstract: In the presence of a Galeazzi fracture, a reduced/stable DRUJ needs to be critically assessed as more than half of irreducible DRUJs in a Galeazzi fracture-dislocation were missed either pre- or intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The current standard of treatment of acute Galeazzi fractures is open reduction and internal fixation of the radius and DRUJ 9–12. Typically, osteosynthesis of the radial fracture is achieved with rigid plate fixation using a 3.5 mm or 4.5 mm dynamic compression plate.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard of treatment of acute Galeazzi fractures is open reduction and internal fixation of the radius and DRUJ 9–12. Typically, osteosynthesis of the radial fracture is achieved with rigid plate fixation using a 3.5 mm or 4.5 mm dynamic compression plate.…”
Section: Discussionmentioning
confidence: 99%
“…In general, fracture shortening >5 mm, location of the fracture at the distal radial third (7.5 or 10 cm from the joint), widening of the DRUJs on posteroanterior view, displacement of the ulnar relative to the radius on the lateral view, and fracture of the ulnar styloid base, have been proposed as preoperative indicators of DRUJ instability [ 3 , 5 , 6 ]. Korompilias AV et al [ 4 ] proposed a three-type classification system based on the retrospective evaluation of 95 patients with Galeazzi fractures: Type I was located at the distal third (69 patients), Type II in the middle third (17 patients), and Type III at the proximal third (nine patients).…”
Section: Discussionmentioning
confidence: 99%
“…In rare instances, the DRUJ joint remains irreducible after fixation of the radial shaft fracture. Yohe NJ et al in 2019 [ 6 ] systematically reviewed the literature and found 17 cases among 12 studies; in dorsally unreduced DRUJs, a block to reduction in most cases (92.3%) was secondary to entrapment of one or more of the extensor tendons, with the remaining cases blocked by fracture fragments. Irreducible volar dislocations due to entrapment of the ulnar head occurred in 17.6% of cases with no tendon entrapment noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Galeazzi fracture dislocation is a fracture of the distal third of the radius with an associated DRUJ dislocation ( Caldwell et al 2019 ). A Galeazzi fracture is typically due to a fall onto an outstretched hand (FOOSH) with the forearm in pronation ( Yohe et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%